Memantine for axial signs in Parkinson's disease: a randomised, double-blind, placebo-controlled pilot study. Issue 5 (16th October 2012) - Moreau, Caroline; Delval, Arnaud; Tiffreau, Vincent; Defebvre, Luc; Dujardin, Kathy; Duhamel, Alain; Petyt, Gregory; Hossein-Foucher, Claude; Blum, David; Sablonnière, Bernard; Schraen, Susanna; Allorge, Delphine; et al.
Abstract : Background: Given that memantine is thought to decrease N-methyl-D-aspartic-acid-related (NMDA) glutamatergic hyperactivity and improve locomotion in rats, we sought to assess the drug's impact on axial symptoms in advanced Parkinson's disease (PD). Methods: We performed a 90-day, randomised, double-blind, study with two parallel arms: 20 mg/day memantine versus placebo (ClinicalTrials.gov:NCT01108029 ). The main inclusion criterion was the presence of a severe gait disorder and an abnormal, forward-leaning stance. The following parameters were analysed under standardised conditions before and after acute administration of L-dopa: gait (stride length as primary criterion), the United-Parkinson's-Disease-Rating-Scale (UPDRS) motor score and its axial subscore, the hypertonia and strength of the axial extensors and flexors (isokinetic dynamometer), the Dyskinesia Rating Scale score (DRS) and its axial subscore. Results: Twenty-five patients were included. The memantine and placebo group did not differ significantly in terms of stride length. However, in the memantine group, we observed significantly better results (vs placebo) for the overall UPDRS score (F(1, 21) =4.9; p=0.039(−1)) and its axial subscore (F(1, 21) =7.2; p=0.014(−1.1)), axial hypertonia, the axial and overall DRS and axial strength. Conclusions: Memantine treatment was associated with lower axial motor symptom and dyskinesia scores but did not improve gait. These benefits must be confirmed in a broader population of patients.